2014
DOI: 10.1002/pts.2117
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Migration of ‘Spiked’ and ‘Intrinsic’ Substances from Paper and Board into Raisins and into Tenax as a Food Simulant

Abstract: Four samples of paper and board (P/B) of a type used for packaging dry foods were subjected to migration experiments using raisins and the polymeric powder Tenax as a food simulant. The P/B samples contained only low levels of diisopropylnaphthalene (DiPN) and diisobutyl phthalate (DiBP), and so, experiments were also conducted after spiking the P/B with added model substances. These were o-xylene, acetophenone, dodecane, benzophenone, DiPN and DiBP. Migration experiments into raisins and Tenax were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Therefore MOSH and MOAH can be found in (nearly) every cardboard packaging material which has been manufactured by use of a certain amount of recycled fibres . Also compounds from printing inks had been found in cardboard packaging materials, from which they can migrate into food or food simulants . The use of functional barriers seem to be a practical way to reduce the contamination of MOSH, MOAH and other contaminants in cardboard packed food.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore MOSH and MOAH can be found in (nearly) every cardboard packaging material which has been manufactured by use of a certain amount of recycled fibres . Also compounds from printing inks had been found in cardboard packaging materials, from which they can migrate into food or food simulants . The use of functional barriers seem to be a practical way to reduce the contamination of MOSH, MOAH and other contaminants in cardboard packed food.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Also compounds from printing inks had been found in cardboard packaging materials, from which they can migrate into food or food simulants. [8][9][10] The use of functional barriers seem to be a practical way to reduce the contamination of MOSH, MOAH and other contaminants in cardboard packed food. Therefore the barrier performance of various packaging films has been investigated recently.…”
Section: Introductionmentioning
confidence: 99%
“…Migration levels in Tenax® depended strongly on the nature of the substance but showed that migration from spiked cardboard was more extensive than migration from contaminated cardboard. It is considered likely that this is because of binding substances present in contaminated cardboard, especially aromatics with pi‐electrons such as DiPN and DiBP, to active sites on the surface of carboardfibres . In this study, Tenax® was found to be an appropriate simulant for the simulation of migration towards raisins …”
Section: Comparison With Real Foodstuffsmentioning
confidence: 88%
“…In 2014, Bradley et al subjected four paper and board samples to migration experiments for DiBP, oX, AP, C10, BP, DiPN and DiBP. Both spiked and unspiked samples were brought into contact with Tenax® for 10 days at 40°C . Migration levels in Tenax® depended strongly on the nature of the substance but showed that migration from spiked cardboard was more extensive than migration from contaminated cardboard.…”
Section: Comparison With Real Foodstuffsmentioning
confidence: 99%
“…Hence, two phthalates (BBP and DBP) and six photo-initiators (BP, DMPA, EDB, ITX, MBP and PBZ) were selected. Futhermore, the following contaminants were also frequently studied: AP, DBS, DiPN, DPBD, DTBP, MS and NPT (Aurela et al, 2001;Bradely et al, 2014 and2015;Isella et al, 2013;Nérin et al, 2007b;Poças et al, 2011;Sanches Silva et al, 2006 andTriantafyllou et al, 2007).…”
Section: Selection Of Contaminantsmentioning
confidence: 99%